ANALISIS NORMATIF PEMBATALAN PERKAWINAN DENGAN ALASAN TERJADI SALAH SANGKA (STUDI PUTUSAN PENGADILAN AGAMA SEI RAMPAH NOMOR 141/Pdt.G/2024/PA.Srh) - Harahap, Az-Zahrotu Zaahin; Siregar, Abdul Rahman Maulana; Sendy, Beby (Universitas Negeri Medan, 2025)
This study develops the interpretation of misunderstanding regarding a husband or wife that can cancel a marriage in Article 27 of Law No. 1 of 1974 in conjunction with Article 72 of the Compilation of Islamic Law. The type of research in this journal is normative legal research with a qualitative approach using a case approach in decision Number 141/Pdt.G/2024/PA.Srh. This study shows that a marriage can be canceled not only limited to falsification of identity but also due to misunderstanding of the nature of the husband or wife, in this case the husband likes the same sex (gay). The results of this case analysis lead to prevention before the cancellation of the marriage occurs through normative solutions that can be applied in marriage law in Indonesia.